Comparison of the Outcomes of Rhomboid Limberg's Flap Rotation versus Simple Excision and Closure of Pilonidal Sinus - Asif, Bakhtawar; Ilyas, Faisal; Fatima, Paras; Arshad, Sohail; Rana, Hummad Naeem; Fatima, Adeeba (Indus Journal of Bioscience Research, 2025)
Background: Pilonidal sinus disease (PSD) is a common chronic condition affecting the sacrococcygeal region, particularly in young adults. Objective: To compare the clinical outcomes of Rhomboid Limberg’s flap rotation versus simple excision and primary closure in patients with pilonidal sinus disease. Methods: This randomized controlled trial was conducted at the Department of Surgery, Shalamar Hospital, Lahore from 1st Nov 2024 to 30th March 2025. A total of 128 patients aged 18–60 years were enrolled using non-probability consecutive sampling and randomized into two equal groups (n=64 each). Group A underwent Limberg flap rotation, while Group B underwent simple excision and closure.  Results: Group A (Limberg flap) showed significantly lower mean pain scores (VAS Day 1: 3.8 ± 1.1 vs. 5.6 ± 1.3), shorter healing time (14.1 ± 3.2 vs. 19.5 ± 4.6 days), and lower infection rate (10.9% vs. 28.1%) compared to Group B. Recurrence rate was also lower in Group A (3.1% vs. 17.2%, p = 0.01). Although operative time was longer in Group A (58.3 ± 10.2 vs. 42.6 ± 8.4 minutes), overall patient satisfaction was higher (4.4 ± 0.6 vs. 3.5 ± 0.9, p < 0.001). Conclusion: It is concluded that Rhomboid Limberg’s flap rotation offers superior outcomes over simple excision and closure for pilonidal sinus disease, including lower recurrence and complication rates, faster recovery, and higher patient satisfaction, despite a longer operative time.